2008
DOI: 10.1158/1078-0432.ccr-07-4366
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical and Pharmacokinetic Study of Kahalalide F Administered Weekly as a 1-Hour Infusion to Patients with Advanced Solid Tumors

Abstract: Purpose: A dose-escalation, phase I study evaluated the safety, pharmacokinetics, and efficacy of a weekly 1-h regimen of kahalalide F, a cyclic depsipeptide isolated from the marine mollusk Elysia rufescens, in adult patients with advanced solid tumors and no standard treatment available. Experimental Design: Patients received an i.v. 1-h infusion of kahalalide F once weekly until disease progression or unacceptable toxicity. The starting kahalalide F dose was 266 μg/m2, and dose escalation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 15 publications
(18 reference statements)
0
48
0
Order By: Relevance
“…Transaminase increases were also reported in phase I trials with the related compound kahalalide F [24][25][26]. An evaluation done with data from the entire clinical development program of elisidepsin, including phase I and II data, showed no serious liver dysfunction as related to elisidepsin; no patients qualified for Hy's law criteria [23].…”
Section: Discussionmentioning
confidence: 99%
“…Transaminase increases were also reported in phase I trials with the related compound kahalalide F [24][25][26]. An evaluation done with data from the entire clinical development program of elisidepsin, including phase I and II data, showed no serious liver dysfunction as related to elisidepsin; no patients qualified for Hy's law criteria [23].…”
Section: Discussionmentioning
confidence: 99%
“…infusion during five days at a dose of 560 µg/m 2 per day once every three weeks [12]. Also in the Phase I clinical stage, another group found that the maximum tolerated dose was 800 µg/m 2 to patients with advanced solid tumors [13]. Recently, a group evaluated the effect of demographics and pathophysiologically relevant factors on KF pharmacokinetic parameters, however, no clinically relevant covariates were identified [14].…”
Section: Green Seaweeds As a Source Of New Bioactive Prototypementioning
confidence: 99%
“…[10]. In phase I and II clinical trials, kahalalide F provided a benefit to patients with advanced androgen-refractory prostate cancer and other advanced tumours [11][12][13][14]. Thus, marine natural compounds with cyclodepsipeptidic structure are of great interest in drug discovery.…”
Section: Introductionmentioning
confidence: 99%